Creation, Death, and the Goodness of God in Augustine's De ciuitate Dei - Djuth, Marianne (Augustiniana, 2025)
This study focuses on two significant themes that underlie the broad dynamics of Augustine’s De civitate Dei, namely, Augustine’s understanding of the relation between creation and human agency, and the correlation between death and the mutability of time. In so doing, it aims to provide deeper insight into Augustine’s Christian anthropology by drawing attention to the significance of the goodness of creation and the evil of death that God entwined in human life owing to divine generosity and the punishment for sin. The first part of the study examines the role that God and human beings play in the propagation of the human race. By distinguishing between intrinsic and extrinsic causes, Augustine is able to balance the internal work of divine omnipotence in creation with the external assistance of human beings in fostering the divine plan. Augustine clarifies the meaning of this distinction by interpreting the passage at 1 Cor. 3,7 in terms of physical reproduction rather than spiritual formation, as Paul does. In the second part of the study Augustine turns his attention to the problem of death and the meaning of terms such as 'death', 'dying', and 'dead'. Eventually, Augustine is able to sort out the meaning of these terms by relying on Scripture, thereby uncovering their true meaning rather than relying on speech and reasoning. On the basis of Scripture, he concludes that dying is similar to the passing of present time that simply disappears and is difficult to detect. Nonetheless, for Augustine, death is a troubling reality that cannot be avoided.